Queer Walking Tours and the affective contours of place. (October 2019) - Truman, Sarah E; Springgay, Stephanie
This article outlines a method we call Queer Walking Tours as site-specific research-creation events. It gives a brief overview of the Queer Walking Tours as method and then describes one specific tour that explored the concepts 'Migration, Militarisms, and Speculative Geology'. Queer Walking Tours offer cultural geography and a range of other disciplines and fields a form of place-based research that draws on Indigenous, anti-racist, feminist, and queer frameworks to open up different conversations around the notion of place.